Assessment of the effects of different extraction methods on the phytochemicals, antimicrobial and anticancer activities of Eruca sativa extracts - Abeer F. Ahmad; Heba A. Shehta (Novel Research in Microbiology Journal)
The present study aimed to investigate the benefits of ultrasonic method of extraction compared to maceration method, on intensifying the phytochemicals, antimicrobial, and cytotoxicity activities of Eruca sativa leaves and sprouts ethanolic extracts. The ultrasonic treatments of E. sativa leaves and sprout, were tested after 10, 20 and 30 min., whereas, maceration treatments of E. sativa leaves and sprout, were considered after 72 h. Results of Gas Chromatography-Mass Spectrometry (GC-MS) analysis showed that E. sativa leaves and sprouts are reach sources of active components such as phenols and flavonoids. Moreover, the sprout macerated extracts showed higher total antioxidant activity (TAA), total phenolic contents (TPC) and total flavonoids (TFC), compared to those of the sprout ultrasonic extracts. On the contrary, the ultrasonic extraction of leaves was more efficient than maceration. Results of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity showed that ultrasonic treated leaves, sprouts (10 min.), and macerated sprouts (72 h), recorded the lowest effective concentrations (EC50) of; 2.77, 3.846, and 3.676 mg/100 ml, respectively. The antimicrobial activity of the extracts was assessed using the well diffusion method. Results showed that ultrasonic treated sprouts (10 min.) and ultrasonic treated leaves (10 and 30 min.) have better antifungal activity against Aspergillus fumigatus (recording diameter of inhibition zone of 13 mm) and Candida albicans (recording diameters of inhibition zones of 13 and 11 mm, respectively). For bacteria, the Staphylococcus aureus was effectively inhibited (recording inhibition zone diameter of 13 mm) by the ultrasonic treated leaves (20 min.), Bacillus cereus was effectively inhibited with ultrasonic treated sprouts (20 and 30 min., both recording 13 mm), ultrasonic treated leaves (10 and 20 min., recording 14, 13 mm, respectively), and the macerated leaves (72 h, recording 13 mm). Salmonella typhimurium recorded (13 mm) with ultrasonic treated leaves (10 min.), and (12 mm) with macerated sprouts. Results of the cytotoxic potency demonstrated high activity of the macerated sprouts on HepG2 cell lines, whereas the macerated sprouts and ultrasonic treated leaves (30 min.) presented high efficacy on the HT-29 cells. Thus we concluded that extracts of E. sativa leaves and sprouts produced using different extraction methods, have a substantial beneficial antioxidant, antimicrobial and anticancer activities.